Research on Simulation and Performance Optimization of Mach 4 Civil Aircraft Propulsion Concept - Min Chen; Zihao Jia; Hailong Tang; Yi Xiao; Yonghang Yang; Feijia Yin (International Journal of Aerospace Engineering)
Supersonic civil aircraft is of a promising area in the development of future civil transport, and aircraft propulsion system is one of the key issues which determine the success of the aircraft. To get a good conceptual design and performance investigation of the supersonic civil aircraft engine, in this article, a fast, versatile as well as trust-worthy numerical simulation platform was established to analyze the Mach 4 turbine-based combined cycle (TBCC) engine concept so as to be applied to the supersonic civil aircraft. First, a quick and accurate task requirement analysis module was newly established to analyze the mission requirement of the Mach 4 supersonic civil aircraft. Second, the TBCC engine performance simulation model was briefly presented and the number of engines on the supersonic civil aircraft was analyzed, considering single engine inoperative. Third, the Stone model and the DLR method were investigated to estimate the engine jet noise and the NOx emission of the Mach 4 supersonic civil aircraft. Finally, a multiobjective optimization tool made up of a response surface method and a genetic algorithm was developed to optimize the design parameters and the control law of the TBCC engine, in order to make the Mach 4 supersonic civil aircraft engine with better performance, lower noise, and lower emissions. The uniqueness of the developed analysis tool lies in that it affords a numerical simulation platform capable of investigating the task requirement analysis module of the supersonic civil aircraft, engine jet noise prediction model, and the NOx emission prediction model, as well as a multiobjective performance optimization tool, which is beneficial for the conceptual design and performance research of Mach 4 supersonic civil aircraft’s propulsion system.